IMPACT OF GLOBALISATION TRANSFORMATIONS ON THE CONSTITUTIONAL AND LEGAL REGULATION OF A PERSONAL LEGAL STATUS - Balayan, Ellada (Revista Inclusiones, 2020)
The goal of this research study is to provide an in-depth analysis of what constitutional and legal regulation of a personal status incorporates as the most important obligation of the present-day national governments with respect to preserving and protecting human values when globalisation processes are underway. A consistent and comprehensive human evolution, redundant politicization of the law, elimination of poverty, fighting for equality, global economic injustice, the search for a new ideal constitutional model, and other problems are relevant and are on the agenda for the entire global society. The countries with different economic levels, historical traditions, cultural origins, and legal systems have various concepts of human rights, freedoms and duties, and introduce them in practice in various ways. These issues are of paramount importance for Russia, which has equal rights being involved in the international intercourse and the system for global governance and international lawmaking. The research paper is written by making use of such general scientific and specific scientific research methods as concrete-historical, logically historical, system-based, comparative law, and others.